2017
DOI: 10.1016/j.cps.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic Ossification and Hypertrophic Scars

Abstract: Burns and trauma lead to extensive superficial and deep soft tissue wounds which are unable to heal perfectly to the pre-injury state. Typically wound healing requires proliferation of cells capable of differentiating into the injured tissue type. As part of the structural requirements for tissue, these cells lay down extracellular matrix (ECM) often in the form of collagens. However, dysregulated cellular proliferation and collagen deposition often leads to wound pathology. Two conditions – heterotopic ossifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 68 publications
0
19
0
1
Order By: Relevance
“…Patients with tHO are faced with debilitating pain, nonhealing wounds, and joint contractures limiting function . We have previously shown that tHO forms via endochondral ossification, and that inhibition of hypoxic signaling reduces tHO through its effects on cartilage production .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with tHO are faced with debilitating pain, nonhealing wounds, and joint contractures limiting function . We have previously shown that tHO forms via endochondral ossification, and that inhibition of hypoxic signaling reduces tHO through its effects on cartilage production .…”
Section: Discussionmentioning
confidence: 99%
“…HO is a condition in which extraskeletal bone forms in response to local tissue injury; although HO has primarily been studied in the context of genetic mutations in type I bone morphogenetic protein receptors [14][15][16][17], it also is known to form in patients after severe trauma without genetic mutations (e.g., traumainduced HO [tHO]) [14,[18][19][20]. Recently, we have shown that tHO is caused by pathologic cellular proliferation and subsequent differentiation through a cartilaginous intermediary [14,20], prompting us to study transforming growth factor-β (TGF-β), a known mediator of cartilage formation [21][22][23][24][25][26][27], in HO.…”
Section: Introductionmentioning
confidence: 99%
“…After extremity trauma, an inflammatory response is mounted at the site of injury that promotes wound healing and regeneration of involved musculoskeletal tissues. However, severe trauma can lead to aberrant wound healing through mechanisms of dysregulated inflammation resulting in fibrosis or stem cell differentiation into a tissue distinct from its original fate, such as heterotopic ossification (HO), which commonly occurs after severe burn or trauma 3 . While the interaction between inflammatory cells and their effect on resident mesenchymal stem cells (MSCs) remains unclear, recent studies have identified MSCs capable of multi-lineage differentiation after injury 4 .…”
mentioning
confidence: 99%
“…Primary outcome of interest for a priori power analysis is volume of mature ectopic bone formation. To detect 50% decrease from 7.5 mm 3 (with standard deviation of 2.2 mm 3 ) in untreated mice at significance level of 0.05 and power of 0.80, at least three mice were required per group. Means and SD were calculated from numerical data, as presented in text, figures, and figure legends.…”
mentioning
confidence: 99%
“…Nearly all the acquired HO developed via endochondral ossification, a biological process usually seen in both bone development and fracture healing. The heterotopic endochondral ossification process triggers with injury/inflammatory, following mesenchymal stromal cell (MSC) recruitment, chondrogenic differentiation, and finally ossification formation [2]. For preventing HO, the inhibition of the chondrogenic differentiation process is most important considering the balance between promoting regeneration and suppression ossification; however, for treating the late-stage HO, the critical points may be the inhibition of osteogenesis and promoting ossification absorption.…”
Section: Introductionmentioning
confidence: 99%